2005
DOI: 10.1159/000084316
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Difference in Size of Brain Regions for Song Learning in Adult Male Dark-Eyed Juncos <i>(Junco hyemalis)</i>

Abstract: In seasonally breeding adult male songbirds, the volumes of several song control regions (SCRs) change seasonally in parallel with plasma testosterone (T) levels and decrease following gonadectomy. Testosterone treatment to castrates prevents this decrease, indicating T dependency. During the breeding season, second-year (SY: birds entering their first breeding season) free-ranging male Dark-eyed Juncos (Junco hyemalis) have smaller testes than older (after second-year, ASY: birds entering at least their secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 109 publications
1
3
0
Order By: Relevance
“…In addition, among the 16 males considered fully recorded in 2002 and also re-recorded in 2003 [average 99 songs ⁄ male (range 27-248) recorded in 2003], we discovered no additional song types, implying that no learning goes on beyond the first year. These results are consistent with the findings of Williams & MacRoberts (1977) who studied a small sample of birds from 1 yr to the next, and Corbitt & Deviche (2005) who compared some known young males with older males.…”
Section: Repertoire Sizesupporting
confidence: 90%
“…In addition, among the 16 males considered fully recorded in 2002 and also re-recorded in 2003 [average 99 songs ⁄ male (range 27-248) recorded in 2003], we discovered no additional song types, implying that no learning goes on beyond the first year. These results are consistent with the findings of Williams & MacRoberts (1977) who studied a small sample of birds from 1 yr to the next, and Corbitt & Deviche (2005) who compared some known young males with older males.…”
Section: Repertoire Sizesupporting
confidence: 90%
“…This age-difference in X volume has not been reported for any species prior to our initial presentation of data on Cassin's finches [MacDougall-Shackleton et al, 2000] and does not occur in starlings [Bernard et al, 1996]. Recently a study of dark-eyed juncos (Junco hyemalis) has shown that SY males have larger area X than ASY males, although the effect size is smaller than that observed in Cassin's finches [Corbitt and Deviche, 2005]. Unlike Cassin's finches, however, the older juncos had longer songs than younger males, but did not sing a greater variety of song syllables.…”
Section: Age Differencesmentioning
confidence: 51%
“…It might be that the most pronounced longitudinal change in best song performance takes place between the second and third years of age (Corbitt & Deviche ; Ballentine ), rather than when the birds are older. Seven birds that were recorded in both years had an age assignment of second‐year in 2006 (plotted as triangles in Fig.…”
Section: Resultsmentioning
confidence: 99%